The influence of epicardial and endocardial use of cryoenergy on the completeness of lesions in surgical ablation of atrial fibrillation - Kurfirst, Vojtech; Csanady, Julia; Mokracek, Ales; Hanis, Jiri; Bulava, Alan; Pesl, Ladislav (Kardiochirurgia i torakochirurgia polska, 2020)
INTRODUCTION: Cryoenergy is the most commonly used method of lesion formation in patients who have undergone surgical ablation of atrial fibrillation. Despite frequent use, the clinical effect of cryoenergy in endocardial and epicardial approaches is unknown. AIM: To compare the effect of various cryoenergy applications on the postoperative incidence of sinus rhythm and completeness of lesions performed. MATERIAL AND METHODS: A total of 55 patients underwent concomitant atrial fibrillation surgical ablation using cryoenergy under various conditions: epicardially during cardiac arrest, epicardially on beating heart, and endocardially. In the postoperative period, patients were invited to attend an electrophysiological examination to assess the completeness of surgical ablation lesions and, if necessary, to complete catheter ablation. RESULTS: Twenty-four patients underwent epicardial ablation on the arrested heart (group 1), 12 patients underwent epicardial ablation on the beating heart (group 2), and 19 patients underwent endocardial ablation (group 3). In the electrophysiological examination, sinus rhythm was present in 71% vs. 83% vs. 89% of patients, respectively. The completeness of pulmonary vein isolation was confirmed in 31% vs. 25% vs. 95% of patients, complete box lesions in 15% vs. 0% vs. 79% of patients, respectively. CONCLUSIONS: Despite the similar clinical effect of surgical ablation in all three approaches, the morphologically most effective use of cryoenergy is endocardial ablation. This approach has a very good result. Our findings further support the endocardial use of cryoenergy during surgical ablation of atrial fibrillation.
Keywords: surgical ablation; atrial fibrillation; cryoenergy